Sustainability Indicators in The Construction of a Triple Bottom Line Kindergarten Building - Diago_Ferrer, Laura; Santolaya, Jose Luis; Muñoz_Lopez, Natalia (International Journal of Sustainable Construction Engineering and Technology, 2025)
The focus of sustainability in the construction sector has typically been on the study of environmental impacts. Considering that sustainability involves a triple bottom line and is based not only on an environmental perspective but also on providing economic and social benefits to stakeholders, the approach based mainly on ensuring the lowest environmental impact should be complemented by introducing socio-economic factors. In this work, the construction process of a nursery school has been analysed in detail and the sustainability has been evaluated using a triple dimensional approach, where environmental, economic and social indicators have been considered simultaneously. The Life Cycle Sustainability Assessment (LCSA) methodology was used to obtain indicators for greenhouse gas emissions, construction costs and working hours, and to provide a comprehensive presentation of the results. The factors that have the greatest impact in each sustainability dimension are identified. In addition, the sustainability triangle is obtained by assigning different weights to the indicators according to the particular interests of the decision-makers, representing the overall sustainability of the building creation. In this way, it is hoped that the impacts caused by residential and commercial buildings can be improved through the criteria of environmental responsibility, economic viability and social equity.